Nurses' perceptions of the role of health organisations in building professional commitment: Insights from an israeli cross‐sectional study during the COVID‐19 pandemic. (28th January 2021) - Goldfarb, Netali; Grinstein‐Cohen, Orli; Shamian, Judith; Schwartz, Dagan; Zilber, Rama; Hazan‐Hazoref, Rivka; Goldberg, Shoshy; Cohen, Odeya
Abstract: Aims: To reveal the factors associated with nurses' professional commitment during the COVID‐19 pandemic. Background: During the first wave of the COVID‐19 pandemic, the Nursing Division at the Israeli Ministry of Health and partners conducted a study to examine the nurses' perceptions towards a set of personal and professional circumstances that may affect their performance. Method: A cross‐sectional Web‐based study was conducted in Israel. Study' participants included 817 community and hospital nurses. The Occupational Commitment Scale for Health Professionals during pandemic (PanHP‐OCS) was used to gather data. Univariate and multivariate analyses explored associations between the PanHP‐OCS score and demographic and professional variables. Results: About 40% of 817 respondents reported having managerial roles ( n = 320). Those who received specific pandemic‐focused training had significantly better PanHP‐OCS scores ( p < .001). Most respondents expected their organisation to provide them emotional support. Linear regression explored the organisational commitment factor as the greatest contributor to nurses' professional commitment (β = 0.284, p < .001). Conclusion: To enhance the nurses' professional commitment during the COVID‐19 pandemic, training and emotional support must be emphasized in all types of nurses' workplaces. Implications for nursing management: In a pandemic, health organisations must provide dedicated pandemic training, including proactive emotional support for nurses. Special attention should be given to community care.